Clinical and genetic spectrums of 413 North African families with inherited retinal dystrophies and optic neuropathies - Aymane Bouzidi; Hicham Charoute; Majida Charif; Ghita Amalou; Mostafa Kandil; Abdelhamid Barakat; Guy Lenaers (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Inherited retinal dystrophies (IRD) and optic neuropathies (ION) are the two major causes world-wide of early visual impairment, frequently leading to legal blindness. These two groups of pathologies are highly heterogeneous and require combined clinical and molecular diagnoses to be securely identified. Exact epidemiological studies are lacking in North Africa, and genetic studies of IRD and ION individuals are often limited to case reports or to some families that migrated to the rest of the world. In order to improve the knowledge of their clinical and genetic spectrums in North Africa, we reviewed published data, to illustrate the most prevalent pathologies, genes and mutations encountered in this geographical region, extending from Morocco to Egypt, comprising 200 million inhabitants. Main body We compiled data from 413 families with IRD or ION together with their available molecular diagnosis. The proportion of IRD represents 82.8% of index cases, while ION accounted for 17.8%. Non-syndromic IRD were more frequent than syndromic ones, with photoreceptor alterations being the main cause of non-syndromic IRD, represented by retinitis pigmentosa, Leber congenital amaurosis, and cone-rod dystrophies, while ciliopathies constitute the major part of syndromic-IRD, in which the Usher and Bardet Biedl syndromes occupy 41.2% and 31.1%, respectively. We identified 71 ION families, 84.5% with a syndromic presentation, while surprisingly, non-syndromic ION are scarcely reported, with only 11 families with autosomal recessive optic atrophies related to OPA7 and OPA10 variants, or with the mitochondrial related Leber ION. Overall, consanguinity is a major cause of these diseases within North African countries, as 76.1% of IRD and 78.8% of ION investigated families were consanguineous, explaining the high rate of autosomal recessive inheritance pattern compared to the dominant one. In addition, we identified many founder mutations in small endogamous communities. Short conclusion As both IRD and ION diseases constitute a real public health burden, their under-diagnosis in North Africa due to the absence of physicians trained to the identification of inherited ophthalmologic presentations, together with the scarcity of tools for the molecular diagnosis represent major political, economic and health challenges for the future, to first establish accurate clinical diagnoses and then treat patients with the emergent therapies.